X‐ray crystal structure of a malonate‐semialdehyde dehydrogenase from Pseudomonas sp. strain AAC. Issue 1 (1st January 2017) - Wilding, Matthew; Scott, Colin; Peat, Thomas S.; Newman, Janet
Abstract : The crystal structure of a malonate‐semialdehyde dehydrogenase from Pseudomonas sp. strain AAC has been determined to a nominal resolution of 2.95 Å. Abstract : The NAD‐dependent malonate‐semialdehyde dehydrogenase KES23460 from Pseudomonas sp. strain AAC makes up half of a bicistronic operon responsible for β‐alanine catabolism to produce acetyl‐CoA. The KES23460 protein has been heterologously expressed, purified and used to generate crystals suitable for X‐ray diffraction studies. The crystals belonged to space group P 21 21 21 and diffracted X‐rays to beyond 3 Å resolution using the microfocus beamline of the Australian Synchrotron. The structure was solved using molecular replacement, with a monomer from PDB entry4zz7 as the search model.